Therapeutic targeting of anoikis resistance in cutaneous melanoma metastasis - Neuendorf, Hannah M.; Simmons, Jacinta L.; Boyle, Glen M. (Frontiers in Cell and Developmental Biology, 2023)
The acquisition of resistance to anoikis, the cell death induced by loss of adhesion to the extracellular matrix, is an absolute requirement for the survival of disseminating and circulating tumour cells (CTCs), and for the seeding of metastatic lesions. In melanoma, a range of intracellular signalling cascades have been identified as potential drivers of anoikis resistance, however a full understanding of the process is yet to be attained. Mechanisms of anoikis resistance pose an attractive target for the therapeutic treatment of disseminating and circulating melanoma cells. This review explores the range of small molecule, peptide and antibody inhibitors targeting molecules involved in anoikis resistance in melanoma, and may be repurposed to prevent metastatic melanoma prior to its initiation, potentially improving the prognosis for patients.